Prognostic Role of ABO Blood Type in Operable Esophageal Cancer: Analysis of 2179 Southern Chinese Patients - Zhang, Shuishen; Jia, Minghan; Cai, Xiaoli; Yang, Weixiong; Liao, Shufen; Liu, Zhenguo; Wen, Jing; Luo, Kongjia; Cheng, Chao (Frontiers in Oncology, 2020)
Background: The prognostic value of ABO blood types is not well clarified for esophageal carcinoma (EC). This study attempted to elucidate the associations between different ABO blood types and disease-free survival (DFS) and overall survival (OS) of EC. Methods: This study was a retrospective review of the records of 2179 patients with EC who received surgery from December 2000 to December 2008. The prognostic impact of ABO blood group on DFS and OS were estimated using the Kaplan-Meier method and cox proportional hazard models. Results: Univariate analyses found significant differences in DFS and OS among the four blood types. Multivariate analyses showed ABO blood type independently predicted DFS (P=0.001) and OS (P=0.002). Furthermore, patients with non-B blood types had a significantly shorter DFS (HR=1.22, 95%CI:1.07–1.38, P=0.002) and OS (HR=1.22, 95%CI:1.07–1.38, P=0.003) than patients with blood type B, and patients with non-O blood types had a significantly better DFS (HR=0.86, 95%CI:0.77–0.96, P=0.006) and OS (HR=0.86, 95%CI:0.77–0.96, P=0.007) than patients with blood type O. Subgroup analyses found that blood type B had a better DFS and OS than non-B in patients who were male, younger, early pathological stages and had squamous-cell carcinomas (ESCC). Blood type O had a worse DFS and OS than non-O in patients who were male, younger, and had ESCC (P<0.05). Conclusions: The results demonstrate that ABO blood group is an independent prognostic factor of survival, and that type B predicts a favorable prognosis, whereas type O predicts an unfavorable prognosis for survival in patients with EC, especially those with ESCC.